Outcome of Internal Fixation of Metacarpal Fractures of Hand at a Tertiary Care Hospital, Kathmandu - Shrestha, Praphulla; Paudel, SR; Chalise, P (Nepal Medical College Journal, 2019)
Hand fractures are different from other fractures elsewhere in the body. Functional impairment of hand leads to a prominent issue to the patient. We have a common practice of treatment of hand fractures by using kirschner wire(s). The internal fixation using plates and screws for metacarpal fractures of the hand is technically demanding but it is beneficial to the patients as it permits early mobilization and better pain relief. We studied the outcome of this type of internal fixation of the metacarpal fractures at Nepal Medical College. We included 26 patients above 18years with isolated extraarticular, closed and open Swanson I metacarpal fractures of the hand. Fractures with rotation of the digit and unacceptable angulation, shortening and unstable fractures were included. Pain was evaluated by visual analogue scale and function using American Society for Surgery of hand Total Active Flexion (ASSHTAF) score. The mean pain score (VAS) was 0.27 at 12 weeks. The ASSHTAF score showed excellent results in 92.3% patients at 12 weeks. At the final follow up 92.3% patients had excellent results, 3.8% had good and 3.8% had poor results. Fracture union was seen in all patients at final follow up. The study shows that internal fixation of unstable metacarpal fractures gives significant pain relief to the patient and an excellent functional outcome.